Profile Clinico Patological of Leprosy at Prof. Dr. I. G. N. G. Ngoerah Central Hospital Denpasar During 2017 – 2022 - Wikaputri, Anak Agung Ayu Mutiara; Saputra, Herman; Ekawati, Ni Putu; Sumadi, I Wayan Juli (Babali Nursing Research, 2024)
Introduction: Leprosy is a chronic disease caused by Mycobacterium Leprae. According to the WHO, leprosy is one of the communicable diseases that affect the skin, peripheral nerves, and upper mucosa, and it can cause physical disabilities, if not properly handled. This study aims to determine the clinical and pathological profile of leprosy at Prof. dr. I. G. N. G. Ngoerah Central Hospital Denpasar, in 2017 - 2022. Metods: The study used a descriptive research design with total sampling from secondary data obtained from the Pathology Anatomy Laboratory of Prof. dr. I. G. N. G. Ngoerah Central Hospital Denpasar. The sample collected during the study period included 63 samples of patients diagnosed with leprosy, which were then processed using SPSS software version 26. Result: The highest number of cases was found in patients age group of 19-64 years, accounting for 55 cases (87.3%), predominantly in male patients with 36 cases (57.1%). The most common main complaint was red patches, with 43 cases (72.8%) presenting erythematous skin lesions, specifically plaques, in 24 cases (42.8%). Conclusion: Based on classification, leprosy was more frequently grouped into two classifications: WHO classification and Ridley Jopling classification. According to the WHO classification, the majority of patients were found to have the PB type, accounting for 35 cases (55.6%), while based on the Ridley Jopling classification, the BT type was more prevalent, with 21 cases (33.3%). This study is beneficial as it provides insights into the clinical and pathological profile of leprosy. Further analytical research is needed to explore the relationships between various variables